Transformasi Peran Perempuan Dalam Hukum Keluarga Islam Di Indonesia - Huda, Afiful; Saifudin, Mohamad (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2024)
This study examines the transformation of Islamic family law in Indonesia, focusing on the application of the Compilation of Islamic Law (KHI) within the framework of Maqashid Syariah, particularly in strengthening gender justice and addressing modern social dynamics. Islamic family law, traditionally rooted in classical fiqh, has undergone adjustments to meet contemporary challenges, such as equality in marriage, child custody, and women's rights protection post-divorce. Although the KHI serves as a primary reference, its implementation faces obstacles, including patriarchal cultural influences, diverse legal interpretations, and gaps in public legal awareness. This study identifies that these transformations are driven by social developments, educational advancements, and the global discourse emphasizing gender equality in Muslim families. Through a critical analysis of the KHI text and its application in religious courts, the study underscores that the transformation of Islamic family law in Indonesia must continue to reflect the values of justice, inclusivity, and relevance to the needs of modern society.